Штрихи до автопортрета (еволюція творчості Юрія Іщенка в контексті стилістичних процесів музичного мистецтва другої половини ХХ століття) - Зав'ялова, О. (Студії мистецтвознавчі, 2007)
This article describes Yuriy Ishchenco's position concerning contemporary music art, his creative approach, professional methods and art principles in the context of stylistic changes in Ukrainian musical art of the second half of the twentieth century.